109k views
0 votes
-2 1/2 x 6 1/2 x 12/39=

User Greg Bacon
by
5.6k points

1 Answer

4 votes

Answer:

-5

Explanation:


-2(1)/(2)\cdot \:6(1)/(2)\cdot \:12/39\\2(1)/(2)\\2(1)/(2)=(2\cdot 2+1)/(2)\\(5)/(2)\\-(5)/(2)\cdot \:6(1)/(2)\cdot \:12/39\\6(1)/(2)\\= 6(1)/(2)=(6\cdot 2+1)/(2)\\((13)/(2)-(5)/(2))\cdot (13)/(2)\cdot \:12/39\\-(5)/(2)\cdot (13)/(2)\\(5)/(2)\cdot (13)/(2)=(5\cdot \:13)/(2\cdot \:2)\\-(5\cdot \:13)/(2\cdot \:2)\\-(65)/(2\cdot \:2)\\-(65)/(4)\\


-(65)/(4)\cdot \:12\\=-(65)/(4)\cdot (12)/(1)\\(65)/(4)\cdot (12)/(1)=(65\cdot \:12)/(4\cdot \:1)\\(65)/(4)\cdot (12)/(1)=(65\cdot \:12)/(4\cdot \:1)\\-(65\cdot \:12)/(4)\\-65\cdot \:3\\= -195\\= -195/39\\-5

User Diego Castro
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.